The effects of self-handicapping on attributions and perceived judo competence - Greenlees, I.; Jones, S.; Holder, T.; Thelwell, R. (Journal of Sports Sciences, 2006)
The aim of this study was to examine hypotheses derived from Jones and Berglas's (1978) self-handicapping model. It was hypothesized that individuals using many self-handicaps would use more internal attributions and report greater gains in perceived judo ability following success than individuals using few self-handicaps. In addition, it was hypothesized that individuals using many self-handicaps would use more external attributions and report less reduction in perceived judo ability following failure. Fifty-three judo players completed measures of trait self-handicapping, situational self-handicapping and a measure of perceived judo ability before competition. Following competition, the participants completed the Causal Dimension Scale II and the measure of perceived judo ability for a second time. Analyses of variance revealed that high self-handicappers attributed failure to more external factors than low self-handicappers. It was also found that high self-handicappers reported less of a reduction in perceived judo ability following failure than low self-handicappers. The findings therefore provide support for the potential short-term benefits of self-handicapping in sport, although further research is required to examine the long-term implications of using self-handicaps.